RESPIRATORY FUNCTIONS IN ASTHMATIC AND NORMAL WOMEN DURING DIFFERENT PHASES OF MENSTRUAL CYCLE - Arora, Dimple Bajaj; Sandhu, Parminder Kaur; Dhillon, Sukhjinder; Arora, Anterpreet; Kaur, Nimarpreet (Pakistan Journal of Physiology, 2015)
Background: Menstrual cycle is an integral part of life of women. There is widespread agreement that changes in the levels of oestrogen and progesterone associated with menstrual cycle also affect different systems of the body besides reproductive system. Levels of oestrogen and progesterone are maximum in the secretory phase and minimum just before the menstruation .Bronchial asthma is one of the commonest chronic respiratory diseases. Premenstrual worsening of asthma symptoms has been reported to affect 33–40% of asthmatic women. This exacerbation of asthma symptoms has been correlated with the oestrogen and progesterone levels. The association between menstrual cycle and lung functions in normal females has also been recognised. The pathophysiology of this process is still not proved. The purpose of our study was to confirm the probable effects of the female hormones on lung functions in normal and asthmatic women in different phases of menstrual cycle and to compare them. Methods: The study was done on 40 normal and 40 asthmatic females in the age group of 15–45 years. Pulmonary function tests were done in three phases of menstrual cycle i.e. follicular, secretory and menstrual in all the subjects. Results: The mean value of lung functions, i.e., FVC, FEV, PEFR, FEF25–75%, FEF200–1200 were significantly lower in asthmatic females than normal ones (p<0.01) in all three phases. The lung functions of both asthmatic and non-asthmatic females in secretory phase were significantly higher than in menstrual phase (p<0.005). The PFTs in menstrual phase were even lower than the follicular phase (p<0.04). Conclusion: Respiratory parameters of both asthmatic and non-asthmatic women in reproductive age group show significant variation in different phases of menstrual cycle. The smooth muscle relaxant effect of progesterone and probably oestrogen might have contributed to it. The lung function parameters in asthmatics were of lower value compared to normal women.